Análise da vulnerabilidade e risco como subsídio ao planejamento urbano : município de Pirambu (SE) - Silva, Adriano Ezequiel (2016)
The city of Pirambu, located in the north shore of the Sergipe state highlights itself because of the relatively preserved natural characteristics. Inside the area of the county, the coastal zone concentrates the biggest interest of the realty agents due to its 23km of shoreline, including some parts that are protected by the environmental law. In the interphase zone the presence of dunes, mangroves, rivers and lagoons stand out, for example, the Sangradouro Lagoon and the Redonda Lagoon. This study has evaluated the environmental risk and vulnerability, with urban focus, of this county. In order to do that a theoretical review approach was made with the fundaments of the Geosystemical method, starting with the theoretical contributions of Bertrand (1971) and the Ecodynamical analysis of Tricart (1977), addressing the mapping and diagnosis techniques proposed by the INPE (National Institute of Space Research), which were adequately adapted to the local reality, complemented by mapping campaigns. As results, a thematic map was made with the interpretations of the geofacies of the studied area, introducing the natural and anthropic risks and the legal restrictions existents in the area, with the finality of subsidize the planning of the soil use and occupation, with suggestions of aptitude for urban purposes in future studies.